Magnetic resonance arthrography of the hip: technique and spectrum of findings in younger patients - Aubry, Sébastien (Springer-Verlag, 2010)
Magnetic resonance(MR) imaging is the reference imaging technique in the evaluation of hip abnormalities. However, in some pathological conditions—such as lesions of the labrum, cartilaginous lesions, femoroacetabular impingement, intra-articular foreign bodies, or in the pre-operative work-up of developmental dysplasia of the hip—intra-articular injection of a contrast medium is required to obtain a precise diagnosis. This article reviews the technical aspects, contraindications, normal appearance and potential pitfalls of MR arthrography, and illustrates the radiological appearance of commonly encountered conditions.